Tepelně technické vady v kontextu možného dopadu na cenu věci nemovité - Hlavsa, Petr; Rašovská, Lucie (Vysoké učení technické v Brně, Ústav soudního inženýrství, 2015)
Thermal technical faults of buildings do not immediately mean life threatening danger in comparison with momentous static faults. However, it’s not possible to underrate them. On the one hand they can carry an increased requirement of energy, on the other they very often endanger sound living conditions and thermal comfort. Even the possible reduction in the esthetic value of a space, which is affected by a fault, is not negligible. The occurrence of surface condensation is a frequent manifestation from fault. Often times this condensation accompanies the formation of mold on the surface of a structure. This article deals with possible ways to detect this kind of a fault, shows feasible data analysis from flaw detection, and suggests possible remedies to eliminate the effects of this fault. These remedies are further analyzed in terms of the potential impact on the price of real estate, namely on the price of dwelling affected by humidity fault.

Tepelně technické vady stavebního objektu neznamenají přímé ohrožení života jako významné vady statické. Nelze je však podceňovat. Na jedné straně s sebou mohou nést zvýšenou energetickou potřebu, na straně druhé velmi často ohrožují zdravé životní podmínky a tepelnou pohodu. Nezanedbatelné je i možné snížení estetické hodnoty vadou postiženého prostoru. Často se vyskytujícím projevem vady je výskyt povrchové kondenzace. Tuto kondenzaci mnohdy doprovází tvorba plísní na povrchu konstrukce. Článek se zabývá možným způsobem detekce tohoto typu vady, uvádí možnou analýzu dat z defektoskopie a navrhuje možná opatření pro vyloučení působení této vady. Tyto opatření jsou dále analyzována z pohledu možného dopadu na cenu věci nemovité, konkrétně na cenu bytové jednotky postižené vlhkostní vadou.
Thermal technical faults in the context of their possible impact on the price of real estate
Keywords: Thernal technics; fault; price of real estate; surface condensation; costs of remediation; dwelling; infrared thermography; Tepelná technika; vada; cena věci nemovité; povrchová kondenzace; náklady sanace; bytová jednotka; infračervená termografie